2022
DOI: 10.3390/agronomy12123112
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile, Bioactivity, and Biosafety Evaluations of Essential Oils and Main Terpenes of Two Plant Species against Trogoderma granarium

Abstract: In order to search for bio-rational and eco-friendly pest control agents to protect crops from insect infestation, while avoiding the toxic hazards of chemical pesticides, essential oils (EOs) were hydrodistilled from Juniperus procera and Thymus vulgaris and analyzed using gas chromatography–flame ionization detection (GC–FID), and gas chromatography–mass spectrometry (GC–MS). Eugenol (71.3%), β-caryophyllene (11.8%), and α-pinene (6.1%) were isolated as the major components of J. procera EO, whereas thymol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…In the present study, enzymes significantly inhibited treated beetles as compared to control. This agreed with Almadiy and Nenaah (2022), who found that oils inhibited acetylcholine esterase in T. granarium larvae. Younes et al (2011) reported that AChE activity changed response to medicinal plant oils.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, enzymes significantly inhibited treated beetles as compared to control. This agreed with Almadiy and Nenaah (2022), who found that oils inhibited acetylcholine esterase in T. granarium larvae. Younes et al (2011) reported that AChE activity changed response to medicinal plant oils.…”
Section: Discussionsupporting
confidence: 92%